Sistem Pengamanan Lembaga Pemasyarakatan Guna Mencegah Peredaran Barang Terlarang - Julia, Hepy; Harun, Rina Rohayu; Erwin, Yulias (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2025)
Correctional institution has an important role in developing inmates to became better individuals ready to return to society. Today, The number of inmates in correctional institutions is a challenge for the Ministry of Immigration and Corrections. Many security disturbances to correctional institution, both from outside and from within, make correctional institution a place that is vulnerable to violations, both from inside and outside the correctional institution. Prohibited goods are something that must be watched out for when entering a correctional institution, this is because it will disrupt the security stability within the correctional institution. The aim of this research is to find out the security system in correctional institution to prevent the circulation of prohibited goods. Research method used in this research is juridical-normative legal research. The result of thus study are the criteria for prohibited goods in correctional institution such as money, valuables, drugs, alcohol, electronic devices dan firearms. Security system against the entry of prohibited goods into the correctional institution, namely Main Doo Security (P2U), inspection of goods and body, establishing rules regarding goods entering the Prison and routine searches.